2014
DOI: 10.1186/1471-2318-14-38
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicine by older adults – a cross-sectional survey

Abstract: BackgroundVery little is known about complementary and alternative medicine (CAM) use by older adults in Germany. The aim of this study was to investigate the use of CAM and other health promoting substances (e.g., herbal teas) by older adults of at least 70 years of age.MethodsA cross-sectional questionnaire study was conducted among persons of ≥70 years from metropolitan Berlin and rural parts of Brandenburg, Germany. Recorded were: demographics, current use of CAM, medical diagnoses, users’ opinions and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 19 publications
7
53
0
10
Order By: Relevance
“…In these studies, the percentage of CAM usage varies between 35.3% and 86.3% [10][11][12][13][14][15] . In studies carried out on elderly individuals, the percentage of CAM usage varies between 27.7% and 88% 8,[16][17][18][19][20][21][22][23][24][25][26] . These methods have been preferred mostly by elderly who are well-educated 3,16,19 have a high socio-economical status 19,20 , are female 17,19,27,28 , and are younger elderly 16 .…”
Section: Araştirma Makalesi̇ / Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…In these studies, the percentage of CAM usage varies between 35.3% and 86.3% [10][11][12][13][14][15] . In studies carried out on elderly individuals, the percentage of CAM usage varies between 27.7% and 88% 8,[16][17][18][19][20][21][22][23][24][25][26] . These methods have been preferred mostly by elderly who are well-educated 3,16,19 have a high socio-economical status 19,20 , are female 17,19,27,28 , and are younger elderly 16 .…”
Section: Araştirma Makalesi̇ / Research Articlementioning
confidence: 99%
“…In this study, we have observed that the elderly have used non-herbal supplements such as honey, vitamins (vitamin B, vitamin C, vitamin D, vitamin E, and vitamin A; respectively), fish oil, royal jelly, magnesium, omega 3-6-9, and coenzyme Q10 at rates differing between 7% and 31.7%. Previous studies showed that elderly individuals mostly use vitamin E 18,20 , Ca 20,26 , magnesium 26 , iron 26 , vitamin C 18,20 , vitamin D 3 26 , B 12 26 , folic acid 26 , chondroitin sulphate 18 and minerals 18 . Our study results are in line with the literature.…”
Section: The Frequency Of Cam Usagementioning
confidence: 99%
See 1 more Smart Citation
“…[15,16] One such study conducted in Texas in breast and other gynecological cancer patients showed the use of CAM to be 48% irrespective of the stage of malignancy while another study on geriatric patients conducted in Germany puts it to be 61.3%. [17,18] Further, the use of CAM therapy in specific groups has been studied such as Hypertensive in South African countries where the utilization was around 51.9-63%. [19] Moreover, Indian population living in South Africa was using CAM in the range of 42.8-48.1%.…”
Section: Growth Of Cammentioning
confidence: 99%
“…In the last few years the number of people that addresses to unconventional therapies and practices is growing. This adherence to alternative medicine is unmistakable marks of escape from the orthodox scientific medicine, a sign of dispute, dissatisfaction, towards to a medical practice that doesn't respect or forget, indeed, the person's and the individual's overall structure [11]. The need for safety and the health's expectations, together with the aspiration of a global well-being, lead to an incessant demand of physical and mental wellness.…”
Section: Cam and Quality Of Life In The Older Adultsmentioning
confidence: 99%